3(-x-10)=-9

Simple and best practice solution for 3(-x-10)=-9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(-x-10)=-9 equation:



3(-x-10)=-9
We move all terms to the left:
3(-x-10)-(-9)=0
We add all the numbers together, and all the variables
3(-1x-10)-(-9)=0
We add all the numbers together, and all the variables
3(-1x-10)+9=0
We multiply parentheses
-3x-30+9=0
We add all the numbers together, and all the variables
-3x-21=0
We move all terms containing x to the left, all other terms to the right
-3x=21
x=21/-3
x=-7

See similar equations:

| 2x^2-11x=9x | | t*100=25 | | 3x+4x-36=180 | | 16=4(8b-6) | | 14a-6a-5a+3a-3a=18 | | 46y+87=180 | | -18p=-17p+20 | | 5x-22+3x+2+4x-10=180 | | B+b-b=9 | | 3/4(12n+12)=54 | | 0.14(y-6)+0.12y=0.02y-2.1 | | 28x^+5x=3 | | -4+5x-17-22x=0 | | 3h-h+2h-2h-h=3 | | 5x-22=60 | | 3x+2=5x=16 | | -16+18t=16+20t | | 5v+6=-9 | | 28=2+6(z-8) | | x/11+17=0 | | 9s-3s-5s=14 | | -19+11j=12j | | 10x+x+x=18 | | -13b=8 | | -l6=(-2)l+9 | | 3x^2+5x+20=16+x+x^2 | | 6b-2b-5b=1+14-7 | | 18d-12d+3D=10 | | x/8+4=-12 | | -7y-13=5y+11 | | –3=4-y/3 | | y-16+2y+118=180 |

Equations solver categories